Rapid recovery from cognitive deficits in abstinent alcoholics: a controlled test-retest study - Mann, Karl; Günther, Arthur; Stetter, Friedhelm; Ackermann, Klaus (Alcohol and alcoholism, 1999)
Abstract. The pattern of cognitive deficits and their time-dependent recovery were investigated in a cohort of 49 male alcohol-dependent patients using a repeat
Gesehen am 19.11.2020